THS–THM DALAM MENINGKATKAN PEMBINAAN KAUM MUDA KATOLIK DI PAROKI KATEDRAL REINHA ROSARI LARANTUKA - Maria Yunita Corebima (JOURNAL OF COMMUNITY DEDICATION, 2026)
Catholic youth are the future generation of the Church who play an important role in both ecclesial and social life. However, rapid societal changes, technological advancements, and the lack of sustainable formation often become challenges in shaping the character and spirituality of young people. One organization that actively contributes to youth formation is THS–THM (Tunggal Hati Seminari–Tunggal Hati Maria). This study aims to examine the role of THS–THM in enhancing the formation of Catholic youth at Reinha Rosari Cathedral Parish, Larantuka. The study employs a participatory approach through regular training activities, spiritual formation, character building, liturgical service, and involvement in social and community activities. The findings indicate that the presence of THS–THM has a positive impact on the development of faith, discipline, responsibility, service spirit, and fraternity among Catholic youth. Through the various programs implemented, THS–THM members become more actively involved in Church life and are able to serve as role models for other young people. Therefore, THS–THM serves as an effective means of forming Catholic youth who are faithful, possess strong character, and are ready to serve both the Church and society.